Esophageal Varices Bleeding in Portal Hypertension due to Portal Vein and Splenic Vein Obstruction - David R.S. Samosir; Loli Simanjuntak; Bambang Setiyohadi; L. A. Lesmana; Aru W. Sudoyo; Marcellus Simandibrata (The Indonesian Society for Digestive Endoscopy, 2002)
Based on its relation to the liver sinusoid, increased pressure of portal vein can occur at three levels: presinusoid, sinusoid ,and postsinusoid. Obstruction of the presinusoid veins can be caused by extra- hepatic condition such as venous thrombosis. We reported a case of portal hypertension with esophageal varices bleeding was a result of obstruction due to thrombosis of the splenic vein and portal vein under hypercoagulant conditions due to thrombocytosis. The management of esophageal varices was sclerotherapy while for overcome the thrombosis the patient was given hydroxy urea. Keywords: esophageal varices bleeding, portal hypertension, vein obstruction